Application of TGT Type Cooperative Model With Kahoot to Improve Cognitive Learning Outcomes of Senior High School Students - Rahmayanti, Dwi; Zulhelmi, Zulhelmi; Putra, Romi (Journal of Indonesian Science Teachers, 2024)
This research aims to determine the increase in student learning gains by implementing the TGT-type cooperative model through Kahoot media on mechanical wave material in class XI SMA N 2 Singingi. The research uses Quasi-Experimental Design type of research with a "post-test only control group design". The instrument used when collecting information was objective test questions on mechanical wave material for class XI high school. The test questions consist of 15 objective questions that refer to 5 cognitive domain indicators. Student learning outcome data is explained both descriptively and inferentially. The learning outcomes of students who applied the TGT model were in a good category, namely 72.8% for the experimental class and 65.9% in the quite good category for the conventional class. So it is concluded that the use of the TGT-type cooperative model assisted by the Kahoot application can improve the cognitive learning outcomes of students in class XI SMA N 2 Singingi.